2017
DOI: 10.1097/pcc.0000000000001031
|View full text |Cite
|
Sign up to set email alerts
|

EMpowerment of PArents in THe Intensive Care Questionnaire: Translation and Validation in Italian PICUs

Abstract: The Italian version of the EMpowerment of PArents in THe Intensive Care questionnaire has satisfactory reliability and validity estimates and seems to be appropriate for Italian PICU setting. It is an important instrument providing benchmark data to be used in the process of quality improvement toward the development of a family-centered care philosophy within Italian PICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
8
1
1
Order By: Relevance
“…Parents from the Malaysian ethnic group rated the items in the domain parental participation the lowest on the 6point rating scale (mean 5.27, SD 0.72). These results are still higher than reported by the EMPATHIC study performed in three Italian PICUs (14). The Italian parents (17).…”
Section: Two Other Parent Satisfaction Instruments Have Been Developecontrasting
confidence: 67%
“…Parents from the Malaysian ethnic group rated the items in the domain parental participation the lowest on the 6point rating scale (mean 5.27, SD 0.72). These results are still higher than reported by the EMPATHIC study performed in three Italian PICUs (14). The Italian parents (17).…”
Section: Two Other Parent Satisfaction Instruments Have Been Developecontrasting
confidence: 67%
“…Our study results mean that the EMPATHIC-30-AUS questionnaire can be used to make comparisons that are specific enough to be meaningful at individual ward and unit level, yet remain standardised to allow benchmarking between hospitals and between countries where validated translation from Dutch has already been conducted such as Italy (20) and Switzerland (19). Indeed, our study results In conclusion, we have confirmed the translated and culturally adapted EMPATHIC-30-AUS to be a reliable and valid questionnaire for paediatric critical care, pediatric and neonatal hospital settings in the Australian context.…”
Section: Discussionmentioning
confidence: 97%
“…We have reported the translation, cultural adaptation and validation of the Dutch EMPATHIC-30 questionnaire into the Australian pediatric critical care, neonatal and pediatric ward areas. We used the standardised translation and cultural adaptation process (16) reported by others evaluating the EMPATHIC questionnaire (19,20) When the results across the 3 clinical areas were combined we found the overall Cronbach α at domain level ranged from 0.70 to 0.82. This reflected the Dutch PICU results which ranged from 0.73 to 0.81 (15) and indicated overall adequate internal consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our study obtained a high response rate (87%). Likewise, the authors of the study that validated the Italian version of EMPATHIC instrument for Pediatric Intensive Care Units (PICU) distributed the instrument to parents at PICU discharge and obtained also a high response rate (79%) compared with postal recruitment [ 27 , 28 ]. In another Italian study, parent satisfaction was evaluated during hospital staying [ 29 ].…”
Section: Discussionmentioning
confidence: 99%